Maternal outcomes in low risk nulliparous women admitted in latent and active phase of labour - Kiran Jabeen (Konselor, 2021)
OBJECTIVE:To determine and compare the frequency of maternal outcomes in terms of augmentation of labour and cesarean section in low risk nulliparous women admitted in latent phase and active phase of labour.STUDY DESIGN:Descriptive case Series conducted from 16th December,2016 to 15th June,2017 at obstetrics and gynaecology Unit-1,Holy Family Hospital, Rawalpindi.METHODOLOGY:130 nulliparous pregnant women in labour fulfilling the selection criteria were included in study at the time of admission in hospital and followed up till delivery and discharge. The study group was stratified in latent and active phase of labour and analysed accordingly. Maternal outcomes were assessed in each woman and recorded in the structured proforma.RESULTS:Frequency of active phase of labour was calculated as 46.92% and latent phase as 53.08%. Comparison of maternal outcome in both groups shows that 29.51% cases of active phase and 56.52% cases of latent phase had caesarean delivery (p=0.002). 70.49% cases of active phase and 49.18% cases of latent phase had vaginal delivery (p=0.002). Augmentation through oxytocin was recorded in 16.39%  in active phase and 31.88% in latent phase (p= 0.04).CONCLUSION:The frequency of maternal outcomes in terms of augmentation and cesarean section in low risk nulliparous women admitted in latent phase is significantly higher when compared to those admitted in active phase of labour. KEYWORDS:Labour, active phase, latent phase, augmentation, maternal outcomes